A 13C solid state nuclear magnetic resonance spectroscopic study of cork cell wall structure: the effect of suberin removal. (International journal of biological macromolecules, 1997)
Solid state 13C NMR measurements of cork, before and after suberin removal, showed that aliphatic suberin is spatially separated from carbohydrate and lignin and experiences higher motional freedom. Two types of chain methylenes, differing in chemical shift and in dynamic properties, were identified in aliphatic suberin. Experimental evidence indicated that the more motionally hindered methylenes are those situated nearer the linkages of aliphatic suberin to the cell wall. These linkages were shown to involve -CH2O- groups, probably engaged in ester linkages to phenylpropane units and carbohydrate C6 carbons. Spectral intensity changes indicated that, during the first steps of alkaline desuberization, these linkages are broken and the shorter aliphatic suberin chains removed. Longer chains require hydrolysis of the ester linkages within the chains and are removed upon stronger alkaline treatment. T1(C), T1 rho (H) and T1 rho (C) relaxation times have shown that the removal of suberin from cork leads to a motionally restricted and more compact environment, on the megahertz and mid-kilohertz timescales. The properties of cork suberin showed that suberin organization in cork is distinct from that in potato tissue.